Penerapan Sasaran Keselamatan Pasien di Rumah Sakit: Literatur Review - Kevin Jodjana; Simon Sia Niha; Henny A Manafe (Universitas Batanghari Jambi, 2023)
This study examines how the literature review regarding the implementation of patient health goals in hospitals. The research used in this research is a qualitative research which is described descriptively. Various sources were processed in this study such as books, research results, journals, and research articles. The results of this study are patient safety is a variable for measuring and evaluating the quality of hospital services that have an impact on health services. One of the safety services in this hospital is the application of patient safety goals which starts with the accuracy of patient identification. This is because patient identification errors at the beginning of the service will continue to the next service error. Patient Safety Goals encourage specific improvements in patient safety including the Hospital Patient Safety Goal Standards. All of this must be done considering the complexity of hospital operations, of course, has the potential for errors. Furthermore, patient safety will have an impact on the patient's medical condition and increase health costs.